Peripheral giant cell granuloma manifestation in pregnancy - Chitra L Patil; Rajesh P Gaikwad; Akshaya B Banodkar; Nilofar B Attar; Gulnar D Sethna (Wolters Kluwer Medknow Publications, 2018)
The peripheral giant cell granuloma (PGCG) is a benign oral lesion occurring on the gingiva and alveolar ridge. It is the most common oral lesion and occurs at an average age of 30 years. The upsurge in the levels of estrogen and progesterone in pregnancy leads to a plethora of changes in various parts of human body, including the oral cavity. In the oral cavity, changes are commonly seen on the gingiva. These include pyogenic granuloma, PGCG and also peripheral ossifying fibroma, etc., The etiology of PGCG in our case might be related to hormonal alterations during the gestation period.